Comparative analysis of cardiorespiratory fitness, bio-motor abilities, and body composition indicators among sprint kayakers of different age groups and expertise levels - Wang, Xiaodong; Zhao, Liqiu (Frontiers in Physiology, 2023)
Abstract This study compared cardiorespiratory fitness, bio-motor abilities, and body composition indexes of sprint kayakers categorized into three different age groups and two expertise levels of international- and club-level athletes. Seventy-three male juniors (n = 14, age = 16.2 ± 0.8), under 23 [U23 (n = 15, age = 20.2 ± 1.6)], professionals (n = 16, age = 27.1 ± 4.8), club-level (n = 15, age = 26.9 ± 6.6), and international-level (n = 13, age = 27.3 ± 3.2) sprint kayakers were studied. Cardiorespiratory fitness (assessed using incremental exercise test), 500 and 1,000-m paddling performance (assessed using kayak ergometer), upper-body power (assessed using 30 s all-out Wingate test) and strength (assessed through one repetition tests for bench press, cable row, and prone bench pull exercises), as well as body composition indexes (measured using dual-energy X-ray absorptiometry) were evaluated on four occasions separated by 48 h recovery. U23 and, especially, professionals indicated significantly (p < 0.05) greater outcomes for the majority of the cardiorespiratory fitness parameters [maximal oxygen uptake (V̇O2max), velocity corresponding to V̇O2max, Oxygen pulse, maximal ventilation, and second ventilatory threshold] and 500 and 1,000-m performance. U23 and professional sprint kayakers significantly (p < 0.05) differed in the first ventilatory threshold and 500, and 1,000-m performance but not in V̇O2max or the second ventilatory threshold. Professionals also showed a lower fat mass, higher muscle mass, and higher strength (bench press, prone bench pull, and seated cable row) and power than U23 and junior kayakers. Strength and power indicators had significantly greater values in U23 athletes compared to juniors. International-level athletes also showed superior V̇O2max, velocity corresponding to V̇O2max, middle (500-m), and long-distance (1,000-m) time trial performance, strength and power, lower fat, and higher muscle mass than club-level sprint kayakers. Cardiorespiratory fitness (particularly ventilatory threshold), body composition, and muscle strength/power are the best differentiating factors for sprint kayakers of different ages and expertise levels. These findings could aid coaches in prescribing training programs focusing on improving determining factors in paddling performance, as well as in predicting performance and identifying talent.